2020
DOI: 10.1097/j.pain.0000000000001921
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 resolves pain hypersensitivity induced by cisplatin by reversing sensory neuron hyperexcitability

Abstract: Understanding the mechanisms that drive transition from acute to chronic pain is essential to identify new therapeutic targets. The importance of endogenous resolution pathways acting as a "brake" to prevent development of chronic pain has been largely ignored. We examined the role of IL-10 in resolution of neuropathic pain induced by cisplatin. In search of an underlying mechanism, we studied the effect of cisplatin and IL-10 on spontaneous activity (SA) in DRG neurons. Cisplatin (2 mg/kg daily for 3 days) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 74 publications
(129 reference statements)
1
74
0
Order By: Relevance
“…Moreover, prevention of chemotherapy-induced allodynia by co-administration of an A 3 AR agonist is IL10 mediated as well [ 53 ]. Notably, we showed recently that the spontaneous resolution of cisplatin-induced neuropathy is dependent on IL10 signaling as well [ 27 ]. Moreover, the resolution of cisplatin-induced neuropathic pain in response to nasal administration of mesenchymal stem cells was also mediated by IL10 [ 3 ], indicating that IL10 signaling to peripheral sensory neurons could represent a common mechanism underlying resolution of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prevention of chemotherapy-induced allodynia by co-administration of an A 3 AR agonist is IL10 mediated as well [ 53 ]. Notably, we showed recently that the spontaneous resolution of cisplatin-induced neuropathy is dependent on IL10 signaling as well [ 27 ]. Moreover, the resolution of cisplatin-induced neuropathic pain in response to nasal administration of mesenchymal stem cells was also mediated by IL10 [ 3 ], indicating that IL10 signaling to peripheral sensory neurons could represent a common mechanism underlying resolution of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Indeed various studies showed that cytokines, such as IL-10 and IL-4 may have direct effects on neurons and control their excitability. 25 - 29 Although IL4-10 FP may have direct analgesic properties through direct effects on sensory neurons, subchondral bone osteoclasts and chondrocytes also contribute to OA pain 30 , 31 and are known to express IL-4 and IL-10 receptors. 13 , 32 , 33 Thus it is likely that the observed analgesic effect of IL4-10 FP is also mediated (in part) through indirect actions through osteoclast and chondrocytes or even other intermediate cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic activity can originate from axons, in particular early after injury, but it can also emerge from the DRG soma (Amir et al, 2005). This likely happens due to changes in expression of ion channels in the DRG neuronal soma (Devor, 2006), or due to signaling events that cause the neuron to generate ectopic action potentials and instability in the resting membrane potential (Devor and Yarom, 2002; Odem et al, 2018; Garza Carbajal et al, 2020; Laumet et al, 2020; Lopez et al, 2021). Our previous work clearly showed that human DRG neuron somata from neuropathic pain patients could display ectopic activity, even after surgical removal and culturing (North et al, 2019).…”
Section: Discussionmentioning
confidence: 99%